Liposome-Nanogel Structures for Future Pharmaceutical Applications: An Updated Review - Kazakov, Sergey (Current Pharmaceutical Design, 2016)
Nature uses combination of lipid bilayers and cross-linked macromolecular networks to achieve workability, multifunctionality, and dynamism in living cells of different types. Despite the concept of liposome-nanogel structures (lipobeads) is known for about 30 years, lipobead-based drug delivery systems are still largely experimental. The data available on nano- and giant lipobeads are reviewed to demonstrate technological achievability of lipobeads and to support the expectations that additional expenses on their production will be reimbursed by the potential advantages of their use. Indeed, lipobeads exhibit the properties attractive for the next generation of drug delivery systems: (i) retaining all the important benefits of polymeric and liposomal drug carriers, the hydrogel core brings mechanical stability and environmental responsiveness to the formulation in one construct, (ii) lipobeaddelivered combination therapy shows no toxicity on intravenously administered mice, accumulation of drug-loaded lipobeads both in the area surrounding tumor and within the tumor itself outside the vasculature, high therapeutic activity at the targeted site, and drastically increased survival, (iii) bipartite structure of lipobeads can provide a number of novel and unique options (e.g., consecutive multistep triggering and combined drug delivery systems). In addition, some ideas on the conceptually new drug delivery systems, new mechanisms of lipobead internalization into the cell and new schemes of drug release regulated by specific signaling are discussed.
Keywords: Liposomes